2019
DOI: 10.1038/s41598-019-43561-4
|View full text |Cite
|
Sign up to set email alerts
|

Combining patch-clamping and fluorescence microscopy for quantitative reconstitution of cellular membrane processes with Giant Suspended Bilayers

Abstract: In vitro reconstitution and microscopic visualization of membrane processes is an indispensable source of information about a cellular function. Here we describe a conceptionally novel free-standing membrane template that facilitates such quantitative reconstitution of membrane remodelling at different scales. The Giant Suspended Bilayers (GSBs) spontaneously swell from lipid lamella reservoir deposited on microspheres. GSBs attached to the reservoir can be prepared from virtually any lipid composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…S2). To test this conjecture, we used the Giant Suspended Bilayer (GSB) system recently developed for quantitative analysis of membrane remodeling (Velasco-Olmo et al, 2019). In agreement with earlier observations (Liu et al, 2011), Dyn2 showed limited tubulation activity on GSBs containing a low PE amount even at 4 mol% PI(4,5)P2 (Fig.…”
Section: Pe Regulates Functional Self-assembly Of Dyn2supporting
confidence: 76%
“…S2). To test this conjecture, we used the Giant Suspended Bilayer (GSB) system recently developed for quantitative analysis of membrane remodeling (Velasco-Olmo et al, 2019). In agreement with earlier observations (Liu et al, 2011), Dyn2 showed limited tubulation activity on GSBs containing a low PE amount even at 4 mol% PI(4,5)P2 (Fig.…”
Section: Pe Regulates Functional Self-assembly Of Dyn2supporting
confidence: 76%
“…The tip was then carefully introduced into a home-made humidity chamber and subjected to 10–20 min incubation at 60 °C. Then the beads were transferred to the observation chamber filled with the working buffer, which was pretreated with bovine serum albumin to prevent lipid attachment to the glass 59 . Upon immersion in the working buffer, lipid or proteo-lipid film swelling was followed as spontaneous GUV or proteo-GUV formation.…”
Section: Methodsmentioning
confidence: 99%
“…A significant drawback of ensemble measurements arises from the compositional heterogeneity of proteoliposome reconstitutions, which hampers quantitative analysis of vesicle properties (including stoichiometry of lipids, sterols, transmembrane proteins) and correlation with protein activity 13 . Giant unilameller vesicles (GUVs, 10-100 µm diameter) are model membrane systems with dimensions comparable to that of a cell, allowing single vesicle analysis directly by microscopy techniques such as fluorescence microscopy, fluorescence correlation spectroscopy or atomic force microscopy [14][15][16][17] . Furthermore, such vesicles can be micro-manipulated for position control or mechanical probing.…”
Section: Introductionmentioning
confidence: 99%